Geografia Bíblica: as categorias de análise da ciência geográfica no contexto bíblico - VINENTE, Ana Raísa Fernandes (Universidade Federal do Oeste do Pará, 2023)
We know that Geography is the science that describes the Earth's surface and seeks to understand the physical, social, economic, political and natural relationships with the society that lives there. In this aspect, the categories of analysis of geography in the biblical context suggest an interesting debate. These categories are divided into landscape, place, region and territory. The Bible reveals historical moments of humanity, with the analysis categories of geography identifying how people lived at that time, what the economy and politics were like and how they related to the environment and how they lived in society. The objective of this research is to characterize the categories of analysis of geographic science implicit in biblical narratives. Relating Geography with biblical narratives, we can identify today how the landscape of that time is still seen, how the feeling of belonging to the place is still strong and considered by humanity, how the region is still economically influential and how the territory is still reason for conflicts. Therefore, there are many biblical singularities that we can currently identify through geography.